1993
DOI: 10.1002/1097-0142(19930601)71:11<3640::aid-cncr2820711128>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient treatment of febrile episodes in low-risk neutropenic patients with cancer

Abstract: Background. Hospitalization and intravenous (IV) broad‐spectrum antibiotics are the standard of care for all febrile neutropenic patients with cancer. Recent work suggests that a low‐risk population exists who might benefit from an alternate approach. Methods. A prospective randomized clinical trial was performed comparing oral ciprofloxacin 750 mg plus clindamycin 600 mg every 8 hours with IV aztreonam 2 g plus clindamycin 600 mg every 8 hours for the empiric outpatient treatment of febrile episodes in low‐ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
112
2
6

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(125 citation statements)
references
References 33 publications
5
112
2
6
Order By: Relevance
“…Thus, in parallel with the development of the definition of low-risk, several studies have demonstrated the feasibility of newer approaches including intravenous antibiotic monotherapy (Pizzo et al, 1986;Sanders et al, 1991;Rolston et al, 1992;Marshall et al, 2000), outpatient ambulatory intravenous therapy (Rubenstein et al, 1993;Talcott et al, 1994) and the use of oral antibiotic regimens (GardembasPain et al, 1991;Malik et al, 1992). These approaches have recently culminated in the publication of two large prospective randomised trials (Freifeld et al, 1999;Kern et al, 1999) that have reported equivalence in terms of both efficacy and safety for an in-patient combination oral antibiotic regimen as compared with standard in-patient parenteral regimen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in parallel with the development of the definition of low-risk, several studies have demonstrated the feasibility of newer approaches including intravenous antibiotic monotherapy (Pizzo et al, 1986;Sanders et al, 1991;Rolston et al, 1992;Marshall et al, 2000), outpatient ambulatory intravenous therapy (Rubenstein et al, 1993;Talcott et al, 1994) and the use of oral antibiotic regimens (GardembasPain et al, 1991;Malik et al, 1992). These approaches have recently culminated in the publication of two large prospective randomised trials (Freifeld et al, 1999;Kern et al, 1999) that have reported equivalence in terms of both efficacy and safety for an in-patient combination oral antibiotic regimen as compared with standard in-patient parenteral regimen.…”
mentioning
confidence: 99%
“…Serial studies at the MD Anderson Center (Rubenstein et al, 1993;Elting et al, 1997) using both intravenous and oral regimens in the outpatient setting have reported both high response rates and low readmission rates. However, these studies have not evaluated outpatient therapy in a randomised comparison with standard in-patient intravenous treatment.…”
mentioning
confidence: 99%
“…9,11,12 Talcott et al 10 showed that the complication rate in patients with fever and neutropenia was 34% if risk factors were present, and only 5% if they were absent. In contrast to studies including patients with an expected neutropenia of Ͻ10 days, 8,13,14 we demonstrate that BC and MM patients up to the age of 63 years in stable clinical condition (Karnofsky у70 ) receiving HDCT with PBSCT who have febrile neutropenia lasting at least 10 days are candidates for outpatient treatment, independent of the underlying disease. The median duration of neutropenia was 11 days in both groups, of which 8 days (group I) vs 7 days (group II) were recorded after beginning of ceftazidime therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying disease and intensive chemotherapy leads to a prolonged neutropenia, a greater frequency of bacteremia, secondary infection, and a risk of death 10 times higher than the patients classified as low-risk (solid tumors and stage I & II lymphomas) [5,7]. These data from different studies allowed low-risk patients to be treated in an ambulatory setting, and emphasized the need of more attention for high-risk patients [6,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%